2022
DOI: 10.3390/biomedicines10061285
|View full text |Cite
|
Sign up to set email alerts
|

The Vascular Microenvironment in Glioblastoma: A Comprehensive Review

Abstract: Glioblastoma multiforme, the deadliest primary brain tumor, is characterized by an excessive and aberrant neovascularization. The initial expectations raised by anti-angiogenic drugs were soon tempered due to their limited efficacy in improving the overall survival. Intrinsic resistance and escape mechanisms against anti-VEGF therapies evidenced that tumor angiogenesis is an intricate multifaceted phenomenon and that vessels not only support the tumor but exert indispensable interactions for resistance and spr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 141 publications
0
23
0
Order By: Relevance
“…Vessel co-option has been reported in both high-grade and low-grade gliomas [ 32 , 38 ]; it appears to occur mainly at the tumor–brain interface and in the peritumor regions, contributing to tumor infiltration [ 21 ]. It might be assumed that vessel co-option and angiogenesis occur where the perivascular niche is set around a vessel with microvascular sprouting or vascular cluster conformation, as in the moderately aggressive GBM types or regions [ 39 ]. Vessel co-option and angiogenesis can occur simultaneously in different areas of the same tumor, or a switch between the two mechanisms can occur over time [ 18 ].…”
Section: Gbm-associated Mechanisms Of Neovascularizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Vessel co-option has been reported in both high-grade and low-grade gliomas [ 32 , 38 ]; it appears to occur mainly at the tumor–brain interface and in the peritumor regions, contributing to tumor infiltration [ 21 ]. It might be assumed that vessel co-option and angiogenesis occur where the perivascular niche is set around a vessel with microvascular sprouting or vascular cluster conformation, as in the moderately aggressive GBM types or regions [ 39 ]. Vessel co-option and angiogenesis can occur simultaneously in different areas of the same tumor, or a switch between the two mechanisms can occur over time [ 18 ].…”
Section: Gbm-associated Mechanisms Of Neovascularizationmentioning
confidence: 99%
“…The tumor microenvironment plays a remarkable role in the transdifferentiation process. The interaction between tumor cells and the endothelium is bidirectional, and their roles seem to be interchangeable, depending on the microenvironment demands [ 39 , 111 ]. A study on human GBM tissues reported the existence of a perivascular niche in which GSCs are close to CD34 + endothelial cells [ 112 ].…”
Section: Gbm-associated Mechanisms Of Neovascularizationmentioning
confidence: 99%
“…Current therapies relying on anti-VEGF mAb usually target tumor angiogenesis. Unfortunately, such therapies have not increased patient survival [ 94 ]. These treatments have been shown to decrease the apelin expression inside the tumor, thus, increasing its invasiveness [ 95 ].…”
Section: A Role Of the Apelinergic System In Brain Diseasesmentioning
confidence: 99%
“…Over time, four microvascular architectures have been identified: microvascular sprouting, vascular cluster, vascular garland, and glomeruloid vascular proliferation [ 9 ]. The first pattern resembles physiological angiogenesis, and its presence denotes a higher survival rate.…”
Section: Introductionmentioning
confidence: 99%
“…The vascular cluster is defined by at least two vessels without interposed stroma. The vascular garland is arranged perinecrotically and consists of neoformation vessels with a circular arrangement [ 9 , 10 ]. The glomeruloid proliferation consists of at least two vessels embedded in the stroma, mimicking the appearance of the glomerulus [ 9 , 11 ].…”
Section: Introductionmentioning
confidence: 99%